Does Auditor Rotation Increase Auditor Independence? - Junaidi Junaidi; Jogiyanto Hartono; Eko Suwardi; Setiyono Miharjo; Bambang Hartadi (Gadjah Mada International Journal of Business, 2016)
This study aims to empirically test the effects of auditor rotation and auditor tenure on an auditor’s independence in companies listed on the Indonesia Stock Exchange during the years 2002-2010. This study using logistic regression estimation technique. The results show that, statistically, the auditor’s tenure has significant negative effects on the auditor’s independence, measured by the tendency to give a ‘going concern’ opinion. Furthermore, the results also show significant differences between the effects of short and long term tenures on the auditors’ independence. Auditor rotation has significant positive effects on the auditors’ independence.